Web-based English grammatical question analysis and retrieval system - Tay, Jin Heng (2014)
The Primary School Leaving Examination (PSLE) is an important milestone for primary school children. English language, the common language in a multiracial society like Singapore, plays an important role. Grammar, a major component, is vital for excellence in the English language. With the advancement in technology, e-learning solutions are becoming the norm. When technology is coupled with traditional teaching methodology, the ease of learning increased manifold. The benefits of web-based learning are that students are able to study on their own pace and comfort level. The proposed system, known as the Grammar Express, hopes to instil the importance of English grammar in students allowing them to learn at their ability level. Topics tested in the PSLE English language examination is investigated and analysed. The English grammar discrete MCQ questions were taken from past year exam papers and assessments books. A wide range of features and functions are also supported to aid students in their learning. Through the analysis of pattern in the different topics, a question storage and retrieval strategy is implemented. In addition, individual questions will be tagged with a difficulty level index through the investigation of readability formulas. The inclusion of an adaptive search mechanism aims to help students find related questions. Furthermore, two testing algorithms will be discussed, along with features such as asynchronous online forum discussion and different question analysers to make Grammar Express a well-rounded e-learning platform. In conclusion, the various components are evaluated and discussed in details. Future developments of the system are also discussed.